PENGARUH SUBTITUSI TEPUNG KIMPUL (Xanthosoma sagitifolium) DALAM PEMBUATAN ROTI - Harnalke Ligo; Jenny Kandou; Christine Mamuaja (COCOS, 2017)
ABSTRACTOne effort to improve food security, namely through the product development process that does not depend on the type of material, but by utilizing local material sources. Purse can be processed into flour for having carbohydrate, protein, fat, with huge potential to be developed and processed into various products sala sole bread. The bread is usually made of wheat flour because it contains gluten. In the purse flour has no gluten so it is used as a substitute. The purpose of this study was to determine the effect of starch concentration purse on the level of development, porosity and quality of the bread and analyze the level of consumer acceptance and chemical analyzes of bread flour purse.This study uses a completely randomized design (CRD). each treatment was performed 3 (three) times repetition with variation flour purse 0% (control), 30%, 50%, 70%, in each treatment and observation of the level of development, porosity, water content, ash content, protein, fats, carbohydrates, and organoleptic test of the level of preference. Results showed the sample A with concentration (Flour 70%: 30% flour purse) has a level of development 2,8cm, porosity 31, the water content of 31.85%, ash content of 1.26%, 4.39% fat content, content 7.02% protein, and carbohydrate content of 54.57% and the highest color organoleptic value of 3.55, 3.50 odor, flavor and texture 3.50 3.40 most preferred panelists. Flour substitution berpengaru purse in high concentrations significantly affected the level of development, the porosity, the quality of bread and panelist preference level, while on the chemical analysis of water content, fat, protein, and carbohydrate, ash content decreases and increases.Keywords: Bread, Gluten, Wheat purse, Wheat Flour.